Tumor Microenvironment: A Metabolic Player that Shapes the Immune Response - Cassim, Shamir; Pouyssegur, Jacques (International journal of molecular sciences, 2019)
Immune cells survey and patrol throughout the body and sometimes take residence in niche environments with distinct cellular subtypes and nutrients that may fluctuate from those in which they matured. Rooted in immune cell physiology are metabolic pathways and metabolites that not only deliver substrates and energy for growth and survival, but also instruct effector functions and cell differentiation. Unlike cancer cells, immune cells are not subject to a “Darwinian evolutionary pressure” that would allow them to adapt to developing tumors but are often irrevocably affected to local nutrient deprivation. Thus, immune cells must metabolically adapt to these changing conditions in order to perform their necessary functions. On the other hand, there is now a growing appreciation that metabolic changes occurring in cancer cells can impact on immune cell functionality and contribute to tumor immune evasion, and as such, there is a considerable and growing interest in developing techniques that target metabolism for immunotherapy. In this review, we discuss the metabolic plasticity displayed by innate and adaptive immune cells and highlight how tumor-derived lactate and tumor acidity restrict immunity. To our knowledge, this review outlines the most recent insights on how tumor microenvironment metabolically instructs immune responsiveness.